Pembuatan Kebijakan Berbasis Bukti: Studi Pada Proses Pembuatan Kebijakan Standardisasi Alat dan Mesin Pertanian di Indonesia - Anugerah Yuka Asmara; Setiowiji Handoyo (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2015)
In Indonesia, generally, policy making is not based on research finding, but it is based on intuition of stakeholders. One evidence based policies that is implemented in Indonesia is policy for standardization of agriculture tools-and-machinery or “Alsintan”. This policy is important for users regarding with work safety and as a barrier of entering of low quality goods from foreign countries. Therefore, the policy for standardization of Alsintan must be formulated with consideration of technical, social, and economic aspects. This policy formulation process involves various actors contributing each other like government, enterprises, experts, and representative organizations. Each actor has his own interest of within formulation process of Indonesian National Standard Alsintan. Nevertheless, actor’s interest in SNI formulation are not partisanship. It means that each actor recognizes the importance of empirical studies and research results as an input at SNI formulation meeting. This research is an empirical study conducted by the way of qualitative-descriptive analysis. This research uses primary and secondary data to support analysis. This research finding is that policy making process for standardization of Alsintan is a collaborative process among actors who have different interests. The role of government is needed to generate and coordinate actors to achieve common goal, based on research results and scientific studies.